Sleep pattern among the medical students in Western Odisha - Giri, Mamata Rani; Sahoo, Arun Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Adequate sleep is required for optimal functioning of human body and mind. Attention and concentration difficulties are related to inadequate sleep among the students. Medical students are considered a stressful group of students because of their hectic schedule. The present study was carried out to know the sleeping pattern among the medical students. Methods: A cross-sectional study was conducted in VIMSAR, Burla, Sambalpur in 2016 among the MBBS Students. Fifty students from each batch were selected by simple random sampling method. Information were collected in a pre-designed pretested questionnaire and was analyzed with Ms-Excel. Results: One hundred and fifty students were selected as the study subjects. The mean bed time during working days was found to be 11:22 pm. Majority of the students 70 (46.6%) were going to bed between 11-12 am. The mean wake up time during working days was 6:52 am and week end was 8:14 am. 75 (50%) students sleep for 6 hours and 42 minutes. 7 (6%) students sleep for 4 hours and 30 minutes. The mean duration of sleep in working days was 6 hours and 46 minutes and in the weekend was 7 hours and 34 minutes. Conclusions: There was less duration of sleep as compared to the recommended sleep duration along with the increase in the mean bed time sleep. It is a concern for the students to prevent the sleep disorder development in future.